Numerical assessment of In-plane behavior of multi-panel CLT shear walls for modular structures - Bhandari, Sujit; Fischer, Erica C.; Riggio, Mariapaola; Muszynski, Lech (Engineering structures, 2023)
•In-plane behavior of multi-panel CLT shear walls for modular structures accessed.•Selected intra- and inter-modular CLT connections benchmarked in OpenSees.•Methodology to benchmark material model using simulated annealing algorithm presented.•Recommendations for reusable CLT structures provided based on finite element modeling. Ponderosa pine (Pinus ponderosa) harvested from restoration forests in the Pacific Northwest region of the United States is being considered for use in cross laminated timber (CLT). A prototype modular building was designed and constructed to assess the feasibility of using such CLT panels in emergency housing that can be rapidly assembled, disassembled, and reused. The modular building uses narrow-width CLT panels connected with intra-modular connections (butt joints with inclined screws) that develop the wall modules, which are connected to each other at the corners with point-type inter-modular connections. To accurately predict the behavior of this modular structure under seismic loading, it is necessary to be able to simulate the connections and wall modules under lateral loading. These selected intra- and inter-modular connections in PP CLT have been mechanically characterized in previous experiments. This paper presents the methodology and results from benchmarking the selected in-plane CLT connections against the experimental data in OpenSees. Further, the impacts of the selected connections on the in-plane monotonic and cyclic behavior of multi-panel CLT shear wall modules are also presented. The results show that the Pinching4 material model in OpenSees, when benchmarked using the simulated annealing algorithm, was able to successfully simulate the selected connections. Simulations of multi-panel wall modules indicate that modules with closely spaced screws in the butt joint behave as a single wall panel, while those with widely spaced screws behave as coupled walls. Recommendations on the spacing of intra-modular connections and the applicability of the modular system using the selected connections are provided based on the finite element analysis.